Research Progress in Environmental Response of Fiber Concrete and Its Functional Mechanisms - Yanxuan Ma; Xia Yu; Fei Zhao; Jin Liu; Pengfei Zhu; Peng Zhang; Jian Zhang; Lei Wu (Advances in Materials Science and Engineering)
Smart fiber reinforced concretes (FRC) are good in intelligent environmental response. With the smart FRC being used in buildings such as bridges and tunnels, the real-time online distributed monitoring of concrete state can be realized. It provides an excellent solution to reduce the emergencies caused by the accumulation of damages, resistance attenuation, etc. This paper analyzes smart FRC’s self-sensing and self-healing response characteristics under different environmental response fields. Furthermore, the intelligent response mechanism of smart carbon fiber reinforced concrete (CFRC), optical fiber reinforced concrete (OFRC), glass fiber reinforced concrete (GFRC), and nanofiber reinforced concrete (NFRC) would be summarized. The response fields include the stress field, temperature field, electromagnetic field, chemical field, and humidity field, among which the field response mechanism of smart NFRC is classified and summarized. Finally, the advantages and disadvantages, the intelligent response parameters, and the applications of smart FRC under different environmental fields are compared.